2000
DOI: 10.1111/j.1559-1816.2000.tb02321.x
|View full text |Cite
|
Sign up to set email alerts
|

Culture and Status as Influences on Account Giving: A Comparison Between the United States and Japan1

Abstract: Being accused of breaking a social norm often forces the accused person to offer an explanation, or an account, for the alleged misdeed. In the present study, American and Japanese participants rated the appropriateness of 4 account types as a function of status of the transgressor and status of the victim. A vignette described a situation in which a person was accused of breaking a promise at work and asked to give an account. While Japanese participants rated apology as significantly more appropriate than di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 22 publications
(30 reference statements)
0
31
0
Order By: Relevance
“…Further, Folkes (1984) showed that before exerting revenge, undergraduate student respondents from the US experienced strong anger; whereas Shteynberg (2005) found that shame emotion was more predictive of revenge than anger for Korean students. Moreover cross-cultural studies on conflict resolution have recognized that collectivists are more likely to prefer non-adversarial strategies to deal with interpersonal conflicts, whereas individualists generally tend to use adversarial strategies over non-adversarial ones (Ohbuchi and Takahashi, 1994;Takaku, 2000). Such findings suggest that consumers from collectivist cultures may be less inclined to seek revenge than their individualist counterparts.…”
Section: Introductionmentioning
confidence: 83%
“…Further, Folkes (1984) showed that before exerting revenge, undergraduate student respondents from the US experienced strong anger; whereas Shteynberg (2005) found that shame emotion was more predictive of revenge than anger for Korean students. Moreover cross-cultural studies on conflict resolution have recognized that collectivists are more likely to prefer non-adversarial strategies to deal with interpersonal conflicts, whereas individualists generally tend to use adversarial strategies over non-adversarial ones (Ohbuchi and Takahashi, 1994;Takaku, 2000). Such findings suggest that consumers from collectivist cultures may be less inclined to seek revenge than their individualist counterparts.…”
Section: Introductionmentioning
confidence: 83%
“…Ohbuchi, 1999;Schoenbach, 1990;Takaku, 2000;Takaku, Weiner, & Ohbuchi, 2001;Weiner, 1995) and have identified the following two types of accounts: (i) responsibility-accepting accounts, such as apology; and (ii) responsibility-avoiding accounts, such as excuse, justification and denial. Ohbuchi, 1999;Schoenbach, 1990;Takaku, 2000;Takaku, Weiner, & Ohbuchi, 2001;Weiner, 1995) and have identified the following two types of accounts: (i) responsibility-accepting accounts, such as apology; and (ii) responsibility-avoiding accounts, such as excuse, justification and denial.…”
Section: Types Of Accountsmentioning
confidence: 99%
“…a motive to avoid harmful consequences, such as a demand for a large amount of compensation, punishment, lowered public trust or lowered self-esteem) (Baumeister et al, 1990;Darby & Schlenker, 1982;Holtgraves, 1989;Itoi, Ohbuchi, & Fukuno, 1996;McLaughlin, Cody, & O'Hair, 1983;Ohbuchi, Kameda, & Agarie, 1989;Ohbuchi, Suzuki, & Takaku, 2003;Schoenbach, 1990;Takaku, 2000;Takaku et al, 2001). a motive to avoid harmful consequences, such as a demand for a large amount of compensation, punishment, lowered public trust or lowered self-esteem) (Baumeister et al, 1990;Darby & Schlenker, 1982;Holtgraves, 1989;Itoi, Ohbuchi, & Fukuno, 1996;McLaughlin, Cody, & O'Hair, 1983;Ohbuchi, Kameda, & Agarie, 1989;Ohbuchi, Suzuki, & Takaku, 2003;Schoenbach, 1990;Takaku, 2000;Takaku et al, 2001).…”
Section: Preferred Accounts By the Perpetrator As Estimated By The Pmentioning
confidence: 99%
“…It would likewise be important to bear in mind that the study utilized a Japanese sample. According to cross-cultural studies, the Japanese people indicate relatively more positive attitudes toward an apology than the North American people (Ohbuchi, Atsumi, & Takaku, 2008;Takaku, 2000). Also worthy to note, the Japanese people may be more prone to attend to the context and make less dispositional inferences than people from individualistic cultures (Miyamoto & Kitayama, 2002).…”
Section: Discussionmentioning
confidence: 99%